CD20+ T cells in monoclonal B cell lymphocytosis and chronic lymphocytic leukemia: frequency, phenotype and association with disease progression - Rodrigues, Cristiana; Laranjeira, Paula; Pinho, Aryane; Silva, Isabel; Silva, Sandra; Coucelo, Margarida; Oliveira, Ana Catarina; Simões, Ana Teresa; Damásio, Inês; Silva, Helena Matos; Urbano, Mafalda; Sarmento-Ribeiro, Ana Bela; et al. (Frontiers in Oncology, 2024)
In Monoclonal B cell lymphocytosis (MBL) and chronic lymphocytic leukemia (CLL), the expansion of malignant B cells disrupts the normal homeostasis and interactions between B cells and T cells, leading to immune dysregulation. CD20+ T cells are a subpopulation of T cells that appear to be involved in autoimmune diseases and cancer. Here, we quantified and phenotypically characterized CD20+ T cells from MBL subjects and CLL patients using flow cytometry and correlated our findings with the B-cell receptor mutational status and other features of the disease. CD20+ T cells were more represented within the CD8+ T cell compartment and they showed a predominant memory Tc1 phenotype. CD20+ T cells were less represented in MBL and CLL patients vs healthy controls, particularly among those with unmutated IGVH gene. The expansion of malignant B cells was accompanied by phenotypic and functional changes in CD20+ T cells, including an increase in follicular helper CD4+ CD20+ T cells and CD20+ Tc1 cells, in addition to the expansion of the TCR Vβ 5.1 in CD4+ CD20+ T cells in CLL.